Gastric pull-up reconstruction combined with free jejunal transfer (FJT) following total pharyngolaryngo-oesophagectomy (PLE). (June 2015) - Ni, Song; Zhu, Yiming; Li, Dezhi; Li, Zhengjiang; Wu, Yuehuang; Xu, Zhengang; Liu, Shaoyan
Abstract: Introduction: Reconstruction following total pharyngolaryngo-oesophagectomy (PLE) still challenges surgeons because of the extreme length of removed tissue. Gastric pull-up reconstruction, one of the most common reconstructive methods after PLE, has many complications such as anastomotic fistula and gastric necrosis caused by the high anastomotic tension. However, modifications of gastric pull-up reconstruction aiming to reducing the high anastomotic tension have been less reported compared with other aspects with this technique. Here we report a modified gastric pull-up reconstruction combined with free jejunal transfer (FTJ) to reduce the anastomosis tension, and thus to reduce the risk of complications after PLE. Methods: Patients underwent a standard surgical procedure including total pharyngolaryngo-oesophagectomy and bilateral internal jugular lymph nodal clearance. A free jejunal graft about 10 cm was harvested and placed in the appropriate position between mobilized stomach and oropharynx. The anastomosis between the free jejunal graft and the gastric tube was created through a stapler. Vascular anastomosis was made between the jejunal artery and the transverse cervical artery, and between the jejunal vein and the internal jugular vein. Hand suturing technique was used in the anastomosis between jejunum and pharynx. Results: None of the patients suffered from any complications such as anastomotic fistula. Both patients resumed early postoperative oral intake. So far, they remain free of tumor recurrence and are in good health for 46 and 18 months, respectively. Conclusion: Considering the tumor status and the patient condition, the gastric pull-up reconstruction combined with FJT after PLE could be a reliable choice. Highlights: Successfully performed a modified gastric pull-up reconstruction. A free jejunal graft placed between mobilized stomach and oropharynx. No complication like anastomotic fistula occurred during follow-up. Gastric pull-up construction combined with FJT after PLE would be a reliable choice.